Analysis of the United Kingdom and the United States' Experience in Ensuring Legality in the Administration of Justice - I. M. Popovych (Bulletin of Kharkiv National University of Internal Affairs)
It is emphasised that in today’s globalised world, legal systems are increasingly oriented towards common values: protection of human rights, ensuring the rule of law, guarantees of judicial independence, transparency of procedures and effectiveness of legal protection. Effective and fair administration of justice is virtually impossible without ensuring its legality. An important aspect in this context is the study of foreign experience, which will allow the most effective models of law enforcement, judicial proceedings and the organisation of the legal system, which have already proven their effectiveness in democratic states, to be borrowed for domestic realities. That is why a comparative analysis will make it possible not only to identify the strengths of foreign legal mechanisms, but also to adapt them to national legal realities, taking into account the cultural, social and legal characteristics of the country.